KEDUDUKAN ANAK ANGKAT TERHADAP HARTA WARISAN DALAM PERSPEKTIF WASIAT WAJIBAH (STUDI PUTUSAN PENGADILAN AGAMA GORONTALO NOMOR 851/Pdt.G/ 2017/PA.Gtlo) - Mohamad Fahri Kolanus; Ahmad Subekti; Nurhasan Nurhasan (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
In the decision number 0851/Pdt.G/2017/PA.Gtlo, the panel of judges decided that the adoption of a child who did not go through a court decision still got 1/3 of the assets of his adoptive parents. , while this is contrary to the legal product. This research presents problems and perspectives that are examined in terms of concepts and behavior in the social world, namely qualitative research with normative legal research types or normative juridical research. The results showed that, First, the position of the adopted child basically cannot take his rights first, but talking about inheritance will be counted again. However, if the adopted child has taken the inheritance, the proceeds will be deducted based on the judge's considerations found in the facts of the trial. Second, the judge's consideration of the psychological aspect is the basis in giving a mandatory will to an adopted child to obtain a third of the inheritance from the adoptive parents. Emotional closeness can describe the devotion of a child to his adoptive parents. Third, the impact in this case should not incriminate the defendant. Because in deciding a case, a judge cannot be intervened or pressured by any party.Keywords: Adopted Child, Position, Mandatory Will